Assessing the market possibilities and productization of ambulatory ECG-devices in the Business to Consumer space - Bryer,Morgan; Palmén,Anton (2023)
There is currently a shift in the healthcare sector moving towards remote monitoring, meaning that monitoring of diseases and other issues is moving out of hospitals and into people's homes with the use of medical technology. One of the fastest-growing at-home monitoring solutions is the ECG device, especially due to the fact that cardiovascular diseases are the leading cause of death worldwide. Currently, the main drivers for this move of at-home (preventive maintenance), monitoring are insurance companies as early detection is cheaper than treating a patient post-complication. This does however not mean that direct consumers are not interested in measuring their vitals, especially cardiovascular health, as more consumer products have started to incorporate ECG readers in for example watches and other wearables. Something that currently is not clear yet is if devices purely intended for measuring these vitals are demanded from consumers, and if there is a willingness to buy these types of devices directly from consumers who have not been prescribed or recommended by a doctor. The target of this study is therefore the assessment of market possibilities of ambulatory ECG devices in the B2C segment. The purpose of this thesis was to assess if there is a market for ambulatory ECG devices in the B2C segment and furthermore what value-added activities customers expect and want in these types of devices. To be able to reach the purpose of the study, an exploratory research strategy was used. The strategy included a case study into a startup, 'Company A', currently developing an ambulatory ECG device. The case study included market research in the shape of interviews with potential customers but also with experts within the industry. Furthermore, two main frameworks were applied to the case, these being the 'Business model Canvas' by Osterwalder and Pigneu and the Kano model developed by Noriako Kano. The conclusion of the study was that currently, two main customer segments are interested in ambulatory ECG devices, these being people who have a cardiovascular disease with a diagnosis and older people who want to keep track of their well-being. Ambulatory devices show some promise in other segments such as people who make a living playing some sort of sport and health conscious people who want to know more about their bodies. For a product of this nature to be successful in these two segments, however, a more extensive value proposition needs to be offered, with features extending beyond the realm of purely ECG readings.
Keywords: ECG; Ambulatory ECG; Medical technology; remote monitoring; B2M.